Acute Toxicity and Neuroprotective Effect of “RJ6601”, a Newly Formulated Instant Soup, in Geriatric Rats - Rujikarn Chaisanam; Jintanaporn Wattanathorn (Foods)
Given its antioxidant effects and central nervous system benefits, we hypothesized that RJ6601 should improve neurodegeneration in the hippocampus, a region critical for cognition and the maintenance of quality of life (QoL). To assure its safety, a single fixed dose of 2000 mg/kg BW was administered to female Wistar rats (250–450 g, 18 months old) to test the acute toxicity of RJ6601. No mortality and toxicity signs were observed. To prove that RJ6601 can protect against age-related neurodegeneration, RJ6601 at doses of 200 and 400 mg/kg BW was administered to the female Wistar rats once daily for 4 weeks. At the end of the study period, assessments were conducted to evaluate the neuron density; MDA levels; and activities of SOD, CAT, GSH-Px, AChE, total MAO, MAO-A, and MAO-B in the hippocampus. Our results reveal increased neuron density, SOD, CAT, and GSH-Px but decreased MDA, AChE, total MAO, MAO-A, and MAO-B in the hippocampi of female Wistar rats subjected to RJ6601 treatment at both doses used in this study. Therefore, RJ6601 is considered to have low toxicity and may improve neurodegeneration as well as cholinergic and monoaminergic dysfunctions. Subchronic toxicity studies and clinical trials are essential to confirm the safety of RJ6601 consumption and its health benefits.